Light induced crosslinking of main chain polybenzoxazines. Issue 40 (28th September 2021) - Deliballi, Zeynep; Kiskan, Baris; Yagci, Yusuf
Abstract : Photo-induced cationic ring opening reactions were performed on main chain polybenzoxazine precursors using iodonium salts. Abstract : Photo-induced cationic ring opening reactions were performed on main chain polybenzoxazine precursors using iodonium salts. Gelation of the precursors was observed in a relatively short time upon photolysis at 300 nm. The obtained gels contained unreacted oxazines and subsequent thermal curing was applied successfully at relatively lower temperatures compared to typical benzoxazines. The main chain polybenzoxazine precursors are shown to have a dual curable character that could be beneficial for deep curing purposes. Moreover, the photocuring wavelength was extended to higher wavelengths using sensitizers such as thioxanthone and camphorquinone in the formulations. All the intermediates and final products were characterized by NMR, FTIR, and UV-Vis spectroscopies and differential scanning calorimetry (DSC) and thermo-gravimetric analysis (TGA) investigation.